2014
DOI: 10.1016/j.cogpsych.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory and the control of attentional control

Abstract: Task-switch costs and in particular the switch-cost asymmetry (i.e., the larger costs of switching to a dominant than a non-dominant task) are usually explained in terms of trial-to-trial carry-over of task-specific control settings. Here we argue that task switches are just one example of situations that trigger a transition from working-memory maintenance to updating, thereby opening working memory to interference from long-term memory. We used a new paradigm that requires selecting a spatial location either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 40 publications
5
51
0
Order By: Relevance
“…Specifically, Bryck and Mayr (2008; see too Mayr, Kuhns, & Hubbard, 2014) have suggested that local task-switching effects may not be due to the residual task set from the previous trial as traditionally argued, but instead reflect an updating of working memory to adjust from the previous task setting stored in long-term memory. Evidence for this process has been found using an asymmetrical-switch task such as the Stroop task in which one task set (e.g., word naming) is dominant over the other non-dominant task set (e.g., color naming).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, Bryck and Mayr (2008; see too Mayr, Kuhns, & Hubbard, 2014) have suggested that local task-switching effects may not be due to the residual task set from the previous trial as traditionally argued, but instead reflect an updating of working memory to adjust from the previous task setting stored in long-term memory. Evidence for this process has been found using an asymmetrical-switch task such as the Stroop task in which one task set (e.g., word naming) is dominant over the other non-dominant task set (e.g., color naming).…”
Section: Discussionmentioning
confidence: 97%
“…The ability to successfully maintain and respond to changing task demands has been suggested to be a distinct executive process that relies upon an efficient top-down control system. This system has been argued to operate by alternating between activating one task set while simultaneously suppressing the other (Miyake, Friedman, Emerson, Witzki, Howerter, & Wager, 2000) and/or an updating process in which working memory transitions from a maintenance to an updating process in accord with the shifting task set (Mayr, 2001; Mayr, Kuhns, & Hubbard, 2014). …”
mentioning
confidence: 99%
“…Importantly, there is evidence from a number of studies that persisting activation from previous task sets interferes with responding to the actual stimulus, particularly when the stimulus has been processed before in the context of the other task (e.g., Waszak et al, 2003;Wylie & Allport, 2000). Interestingly, such costs are not restricted to switch trials, but often occur even on no-switch trials in the context of task-switch blocks (e.g., Mayr, Kuhns, & Hubbard, 2014;Rubin & Meiran, 2005). The present findings constitute an important extension of this pattern of results, because they indicate that in switching situations, interference from previous control settings affects not just the speed of responding to a given stimulus, but also the fidelity with which this stimulus is coded in WM.…”
Section: Discussionmentioning
confidence: 99%
“…A major source of such costs is stimulus-induced interference due to long-term memory representations of the task sets that are used within the same experimental context (e.g., Mayr, Kuhns, & Hubbard, 2014;Rubin & Meiran, 2005;Waszak, Hommel, & Allport, 2003). Similarly, in WM situations that require different filter settings, proactive interference from the currently irrelevant setting may make efficient filtering difficult, even when the currently relevant setting is fully implemented.…”
mentioning
confidence: 99%
“…This may refer to attentional control (Astle & Scerif, 2009) also named endogenous attention or endogenous attentional selectivity (Mayr et al, 2014;Theeuwes, 1991). This psycho-cognitive process supposes the subject is choosing where the attention will be focused and what will be left aside during the activity.…”
Section: Attentional Control Focusing Effect and Sof-based Attentionmentioning
confidence: 99%